EFICIÊNCIA REPRODUTIVA EM EQUINOS DA RAÇA MORGAN - TISA ECHEVARRIA LEITE; MÁRCIA DE OLIVEIRA KARAM; LEONARDO PORTO ALVES; CLÁUDIO ALVES PIMENTEL; SANDRA MARA DA ENCARNAÇÃO FIALA (Ciência Animal Brasileira, 2011)
The purpose of this paper was to describe the following reproductive parameters observed in mares of the Morgan breed: pregnancy rate (TP), foal rate (CP), average length of the gestation (DG), age at the first parturition (IPP), age (ID), interval from parturition to first service (IPPC) and interval from parturition to conception (IPC), foaling interval (IEP), number of cycles per conception (NC) andservices per conception (NS), embryo mortality rate (ME), abortion (A), month of the conception and parturition. Data was obtained from 42 mares in 1 4 years. Values obtained were: TP 71%; ME 6.2%; A 2.4%; DG 340.2 days; IPP 4.5 years; ID 7.6 years; IPPC 1 9.0 days;IPC 27.2 days; IEP 374.0 days; NC 1.2 and NS 3.0. The frequency of utilization of the foal heat was 76.1%. The distribution of mating and parturition, in the breeding season, was concentrated in the months of September to December (78.9 and 87.1%, respectively). These datamay be useful to genetic improvement of the breed as well as to indicate areas in which research must concentrate for a more profitable husbandry